2002
DOI: 10.1128/cdli.9.2.320-323.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Associated Interleukin-8 in Cord Blood of Term and Preterm Infants

Abstract: To assess the effect of gestational age and labor on the interleukin-8 (IL-8) concentration in whole cord blood and serum, IL-8 levels were determined simultaneously in cord blood serum and lysate in 134 infants. Following the elimination of some of the samples due to exclusion criteria, the data for 99 uninfected infants (71 term and 28 preterm) and 9 infants with neonatal bacterial infection delivered either vaginally or by elective or emergency cesarean section were analyzed. The effects of labor and gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In agreement with observations of Dembinksi et al [28], plasma IL-8 was not influenced by gestational age, in contrast to DLWB IL-8; late preterm neonates had lower DLWB IL-8 concentrations ( fig. 1).…”
Section: Disclosure Statementsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with observations of Dembinksi et al [28], plasma IL-8 was not influenced by gestational age, in contrast to DLWB IL-8; late preterm neonates had lower DLWB IL-8 concentrations ( fig. 1).…”
Section: Disclosure Statementsupporting
confidence: 81%
“…In our group of spontaneous births (table 2), we also registered the duration of labor and found no correlation between either DLWB or plasma IL-8 concentrations (not shown); however, we did not analyze or standardize labor pain. Dembinski et al [28] found more evident neonatal proinflammatory response to labor stress in concentrations of IL-8 in whole blood than in serum.…”
Section: Influence Of Hematocritmentioning
confidence: 99%
“…No previous studies have identified increased IL‐12 levels in the plasma of newborns with infection. The present study shows that elevation of this cytokine and IL‐6, IFN‐ γ and IL‐1 β are associated with neonatal infection and may be more sensitive than IL‐8, a cytokine that has reportedly been increased in several studies [2,4]. However, much larger numbers are required to clarify any statistical significance between individual cytokine sensitivity for neonatal infection with other confounding conditions such as inflammatory diseases.…”
Section: Discussionmentioning
confidence: 65%
“…It is well documented that certain chemokines such as CXCL1, CXCL8, and CCL2 mainly present as a cell-bound form in the circulation during various physiological and pathological conditions [3436]. The cell-bound chemokines function as a reservoir to maintain and adjust their systemic and local level.…”
Section: Discussionmentioning
confidence: 99%